Methods of neuromodulation in the treatment of spastic syndrome and their role in complex rehabilitation of patients after spine and spinal cord injuries - Ninel, Vyacheslav; Smol’kin, Аleksey; Korshunova, Galina; Norkin, Igor (Khirurgii︠a︡ pozvonochnika = Spine surgery, 2016)
Objective. To present an algorithm for consistent application of neuromodulation techniques to improve the effectiveness of spastic syndrome relief and to specify its role in the rehabilitation of patients after spine and spinal cord injuries. Material and Methods. The study included 105 patients with increased muscle tone after spinal cord injury. To relieve mus- cle spasticity, a staged therapy was performed including electrical stimulation of the spinal cord, simultaneous epidural drug therapy with electrical stimulation, and local hypothermia of the spinal cord. Results. Positive results were obtained after each stage of neuromodulation therapy. They became a basis for the develop- ment of an algorithm of surgical treatment of patients with excessive muscle spasticity. Conclusion. The proposed algorithm for consistent application of neuromodulation techniques in patients with spastic syndrome after spinal cord injuries allowed significant reducing the degree of spasticity and creating conditions for further rehabilitation in 88.6 % of cases.